Butterfly community structure in a rehabilitated post-mining tropical rainforest landscape, Sorowako, South Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nuraeni S, Prastiyo A, Larekeng SH, Ardiansyah A, Aldi, Jufri SW. 2025. Butterfly community structure in a rehabilitated post-mining tropical rainforest landscape, Sorowako, South Sulawesi, Indonesia. Biodiversitas 26: 4761-4774. Human disturbances, such as mining, can disrupt butterfly communities, which serve as important ecological indicators. This study evaluated butterfly diversity and richness in conservation and non-conservation zones within the mining area of PT Vale, South Sulawesi, Indonesia. Data analysis involved diversity indices, t-tests, and Pearson correlations, with cluster analysis grouping sites and PCA exploring links between butterfly abundance and microclimatic factors. A total of 40 butterfly species belonging to five families, mainly Nymphalidae, Pieridae, and Lycaenidae, were recorded from 18 sampling transects during a four-week field period using standard transect and sweep net methods. The most frequently recorded species was Catopsilia pomona (Pieridae) with a relative abundance of 20.00%, followed by Ideopsis juventa (Nymphalidae) with 19.80%. Results showed that non-conservation sites had slightly higher diversity (1.43±0.67), richness (5.63±4.94), and evenness (0.48±0.13), while dominance was higher in conservation transects (0.52±0.32). This spatial comparison suggests that human-made habitats may support butterfly diversity but also lead to increased species dominance in more intact environments. The t-test showed a significant difference only in evenness. No significant correlations were found between biodiversity indices and environmental variables based on Pearson's analysis. Cluster analysis identified two main site groups: the first included most conservation transects (SC2, SC5, SC6) and some non-conservation transects (SN2, SN3), while the second contained most non-conservation transects and a few conservation sites (SC4, SC8), indicating overlapping habitat features. PCA revealed that light intensity explained 90.15% of the variation in the first principal component, and altitude explained 79.24% in the second, demonstrating their strong influence on butterfly distribution. These results provide baseline data on butterfly community structure and highlight the ecological differences between conservation and disturbed zones.
Keywords: Community composition, conservation, post-mining rehabilitation, South Sulawesi, tropical insects